Appearance-based Discrimination at the Workplace - Barthwal, Tripti; Srivastava, Akanksha (Gyan Management Journal, 2015)
It is a well know fact that an individual's appearance forms the basis for a first impression. It also  affects perceived characteristics such as intelligence, education, wealth and competence. In fact, it's an  almost automatic response to associate attractive individuals with better lifestyles, careers and  education. The workplace is no exception to this phenomenon. This paper explores the issue of  appearance discrimination in workplace. It starts with an assessment of such discrimination and then  examines the impact of such discrimination on the employees, organizational functioning, growth &  career advancement, etc. The paper is based on a study conducted by the authors in which they  surveyed people working across diverse organizations to find out whether appearance based  discrimination is a truth or not, whether respondents have themselves practiced or faced it, etc. The  findings of the study reveal that discrimination based on appearance is a reality in organizations &  females face this more than males.
Keywords: Looks; Discrimination; Appearance; Attractiveness